2011
DOI: 10.1186/1475-2875-10-134
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of malaria among children in southern highland Rwanda

Abstract: BackgroundIncreased control has produced remarkable reductions of malaria in some parts of sub-Saharan Africa, including Rwanda. In the southern highlands, near the district capital of Butare (altitude, 1,768 m), a combined community-and facility-based survey on Plasmodium infection was conducted early in 2010.MethodsA total of 749 children below five years of age were examined including 545 randomly selected from 24 villages, 103 attending the health centre in charge, and 101 at the referral district hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
81
4
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(112 citation statements)
references
References 43 publications
24
81
4
2
Order By: Relevance
“…It was found that older children 24 months and above were more likely to have malaria when compared to children aged 6-11 months. This is similar to other studies, which indicated that an older child was associated with a higher risk of malaria [7,10,11]. Age of child could also contribute to the individual's way of life, where older children could move about freely and may go outside more often and therefore may be more susceptible to mosquito bites, and thus malaria.…”
Section: Socio-economic and Demographic Risk Factorssupporting
confidence: 78%
“…It was found that older children 24 months and above were more likely to have malaria when compared to children aged 6-11 months. This is similar to other studies, which indicated that an older child was associated with a higher risk of malaria [7,10,11]. Age of child could also contribute to the individual's way of life, where older children could move about freely and may go outside more often and therefore may be more susceptible to mosquito bites, and thus malaria.…”
Section: Socio-economic and Demographic Risk Factorssupporting
confidence: 78%
“…20 records met our inclusion criteria (table), [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and of these 15 contained the necessary data for inclusion in the quantitative analysis (meta-analysis). Five records were excluded from the quantitative analysis either because Bayesian credible intervals were reported (n=2) or because ORs could not be calculated from the available data (n=3)[A: sentence correct as edited?].…”
Section: Resultsmentioning
confidence: 99%
“…Arg allele frequencies (Ghana, 0.30; Rwanda, 0.31) and genotypes did not differ between P. falciparum infected and non-infected subjects. Adjusting for the age difference between infected and non-infected individuals and for further associated factors, 8,9 the lack of association between TP53 genotypes and P. falciparum infection remained (data not shown). Likewise, there was no association between genotypes and peripheral blood geometric mean parasite density (/μL, 95% confidence interval [CI]), in either pregnant women (Pro/Pro,1,346]; Pro/Arg, 675 168]; Arg/Arg,1,690]; P = 0.52) or in children [1,837 (978-3,449]; 968 [404-2,322]; 6,792 [615-75,062]; P = 0.12).…”
mentioning
confidence: 99%
“…8 The second group involved 545 children 5 years of age randomly selected from 24 rural villages in southern highland Rwanda of whom 16.1% were P. falciparum infected (by PCR; 2.9% categorized as symptomatic malaria defined as a positive blood film plus fever, or a history of fever within the preceding 48 hours). 9 All participants (or legal guardians) gave informed consent, and the study protocols were approved by the Committee on Human Research Publications and Ethics, School of Medical Sciences, University of Science and Technology, Kumasi, Ghana, and the National Ethics Committee, Republic of Rwanda, respectively. The DNA was extracted from stabilized blood samples (AS1 and QIAmp DNA Blood Mini Kit; Qiagen, Hilden, Germany).…”
mentioning
confidence: 99%
See 1 more Smart Citation